The environmental education and socio-environmental responsibility in the environmental practices in higher education institutions of Brazil - Maneia, Arismar; Cuzzuol, Vera; Krohling, Aloisio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611708786 This article deals with the Environmental Education as part of social-environmental responsibility actions of Higher Education Institutions from the analysis of a few meanings of environmental problems. These institutions need to know the various educational and organisational processes and the subjects involved to define the lines guiding environmental practices guidelines, with an educational method that creates the conditions for individuals to have a real learning for environmental practices aware and committed. The Higher Education Institutions should fulfill their environmental and social responsibility as they have committed to train professionals for the new labour market with vision focused on environmental issues, aware of their social role. Environmental Education represents a strong ally of the institutions that work with education, with the aim of balancing the man and his environment, being a tool for transformation.